2018
DOI: 10.5194/acp-18-16173-2018
|View full text |Cite
|
Sign up to set email alerts
|

TM5-FASST: a global atmospheric source–receptor model for rapid impact analysis of emission changes on air quality and short-lived climate pollutants

Abstract: This paper describes, documents, and validates the TM5-FAst Scenario Screening Tool (TM5-FASST), a global reduced-form air quality source-receptor model that has been designed to compute ambient pollutant concentrations as well as a broad range of pollutant-related impacts on human health, agricultural crop production, and shortlived pollutant climate metrics, taking as input annual pollutant emission data aggregated at the national or regional level. The TM5-FASST tool, providing a trade-off between accuracy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 91 publications
1
75
0
Order By: Relevance
“…In addition to the climate impacts, reducing BC emissions also has positive effects on human health. Using the model TM5-FASST (Huijnen et al, 2010;Van Dingenen et al, 2018) we found that globally 329000 and 402000 premature deaths could be prevented by 2030 and 2050, respectively, if the proposed emission reductions (Stohl et al, 2015;Klimont et al, 2017) would https://doi.org/10.5194/acp-2019-864 Preprint. Discussion started: 7 October 2019 c Author(s) 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the climate impacts, reducing BC emissions also has positive effects on human health. Using the model TM5-FASST (Huijnen et al, 2010;Van Dingenen et al, 2018) we found that globally 329000 and 402000 premature deaths could be prevented by 2030 and 2050, respectively, if the proposed emission reductions (Stohl et al, 2015;Klimont et al, 2017) would https://doi.org/10.5194/acp-2019-864 Preprint. Discussion started: 7 October 2019 c Author(s) 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The aerosol direct radiative effect (DRE) is calculated online by performing the radiation calculations twice, once with and once without accounting for aerosol-radiation interaction. The aerosol direct radiative forcing (DRF) is then again with the chemical transport model TM5 (Huijnen et al, 2010), which accounts for the effects of meteorology and chemical and physical processes on the transport of particulate matter (PM) (Van Dingenen et al, 2018). The source-receptor relationships…”
Section: Climate Simulationsmentioning
confidence: 99%
“…To compute pollutant concentrations from pollutant emission scenarios, we use the TM5-FASST model 77 , a reduced-form air quality assessment tool, built on pairwise emission–concentration sensitivities (so-called source–receptor coefficients (SRCs)) between 56 source regions and individual 1°×1° receptor grid cells for each relevant emitted pollutant or precursor.…”
Section: Methodsmentioning
confidence: 99%
“…In general, chemical processes leading to secondary pollutants involving multiple precursors are non-linear and the embedded linearisation in TM5-FASST may lead to biased estimates of PM 2.5 concentrations and ozone mixing ratios. However, validation studies 77 have shown that the linearity assumption in TM5-FASST holds sufficiently well for regionally averaged (population-weighted) PM 2.5 and ozone responses to precursor emission changes that deviate from −80% to +100% from the reference emissions.…”
Section: Methodsmentioning
confidence: 99%
“…We employ the global linearized atmospheric chemistry transport model TM5-FASST (Van Dingenen et al 2018). It is derived through perturbation runs from the full chemical transport model TM5.…”
Section: Atmospheric Chemistry Transport Modelingmentioning
confidence: 99%